2020
DOI: 10.46328/ijemst.v8i2.674
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Conversations in a WhatsApp Group Created for Communication in a Bachelor’s Level Astronomy Course

Abstract: The aim of this research on an astronomy course is to examine the situations that arose when WhatsApp, a social media application, was used as a tool for cooperation and interaction. In this work, a case study design was adopted. The WhatsApp group created for the research was composed of 87 participants and the messages exchanged in the WhatsApp group were used as research documents. Data were analyzed through descriptive and content analysis methods. The sharing in the WhatsApp group and the topics of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Saritepeci et al ( 2019 ) reported that the students used the WhatsApp group for information sharing and extracurricular activities. While Yuzbasioglu et al ( 2020 ) reported that the students increased their academic knowledge via exchanges in a WhatsApp group, Saritepeci et al ( 2019 ) emphasised that students’ learning in WhatsApp groups tend to be superficial rather than meaningful.…”
Section: Introductionmentioning
confidence: 99%
“…Saritepeci et al ( 2019 ) reported that the students used the WhatsApp group for information sharing and extracurricular activities. While Yuzbasioglu et al ( 2020 ) reported that the students increased their academic knowledge via exchanges in a WhatsApp group, Saritepeci et al ( 2019 ) emphasised that students’ learning in WhatsApp groups tend to be superficial rather than meaningful.…”
Section: Introductionmentioning
confidence: 99%
“…Students consider social media valuable as it facilitates participation in class discussions (Neier & Zayer, 2015). WhatsApp, in particular, is one of the tools students use for extracurricular interaction and communication (Bozdemir Yuzbasioglu, Candan Helvaci, Ezberci Cevik, & Kurnaz, 2020). Online platforms are known to make language learning an easier, interactive, and interesting process (Faizi, El-Afia, & Chiheb, 2013).…”
Section: Introductionmentioning
confidence: 99%